2015
DOI: 10.1038/srep10788
|View full text |Cite
|
Sign up to set email alerts
|

Local proliferation is the main source of rod microglia after optic nerve transection

Abstract: Microglia are the resident phagocytic cells with various functions in the central nervous system, and the morphologies of microglia imply the different stages and functions. In optical nerve transection (ONT) model in the retina, the retrograde degeneration of retinal ganglion cells (RGCs) induces microglial activations to a unique morphology termed “rod” microglia. A few studies described the “rod” microglia in the cortex and retina; however, the function and origin of “rod” microglia are largely unknown. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 25 publications
4
55
0
Order By: Relevance
“…We showed that bipolar/rod-shaped microglia aligned only within the scratched area of the PDL/laminin-coated surface, and the alignment patterns were similar to those observed in the brain after CNS injury in vivo 91016. The microglia became amoeboid on the non-scratched area of the PDL/laminin-coated surface5.…”
supporting
confidence: 69%
“…We showed that bipolar/rod-shaped microglia aligned only within the scratched area of the PDL/laminin-coated surface, and the alignment patterns were similar to those observed in the brain after CNS injury in vivo 91016. The microglia became amoeboid on the non-scratched area of the PDL/laminin-coated surface5.…”
supporting
confidence: 69%
“…In another mouse model of amyotrophic lateral sclerosis that represented chronic, long-lasting damage, these same results were achieved [13]. Consistent with these findings, local proliferation of resident microglia, rather than the infiltration of peripheral monocytes or HSCs, was the major source of Brod^microgliosis in an optical nerve transection model using parabiosis rats [33]. Taken together, the maintenance of the CNS microglia pool only relies on the resident cells without irradiation and BM transplantation and is irrelevant to the timing of microgliosis.…”
Section: Maintenance Of Microglia Poolsupporting
confidence: 85%
“…It is also important to highlight that rod microglia formed with limited proliferation. This is in contrast to other contexts, such as retinal rod microglia following optic nerve crush, where rod microglia result from proliferation (Yuan et al, ). Collectively, these data show that rod microglia develop from resident microglia that were present at the time of injury and underwent structural transformation in response to neuronal injury.…”
Section: Discussionmentioning
confidence: 79%
“…Rod‐shaped microglia form as early as 1 dpi, peak in the subacute window, and align linearly in the cortex 7 dpi (Taylor, Morganti‐Kossmann, Lifshitz, & Ziebell, ). This structure is observed in other pathological contexts, including aging and chronic viral infection (Bachstetter et al, ; Ji, Schachtschneider, Schook, Walker, & Johnson, ; Sierra et al, ; Yuan, Liang, Peng, Lin, & So, ). Thus, it may represent a conserved response to neuronal degeneration/damage.…”
Section: Introductionmentioning
confidence: 81%